Adams – Oliver Syndrome - Joshi, Avadhesh; Karnawat, Bhag Singh; Jangid, Manoj Kumar (Journal of Nepal Paediatric Society, 2016)
Aplasia cutis congenita is characterized by congenital absence of portion of skin over a localized or widespread area. Adams- Oliver syndrome (subtype-II of ACC) is associated with distal limb reduction anomalies. We describe an infant with this uncommon disease associated with multiple midline lesions, which is a rare occurrence. J Nepal Paediatr Soc 2015;35(2):168-171